Control Over Land Owned By Others Reviewed From Criminal Law - Idah Yani Gea; Kasiria Lafau; Jenda Ingan Mahuli (IHSA Institute, 2023)
The purpose of this research is to determine the tenure over other people's land in terms of criminal law. The type of research in this paper is qualitative-normative with a legal (conceptual) approach. Meanwhile, the approach in this research is analytical descriptive. The data used are secondary and primary data. Primary data is in the form of laws and regulations such as the Criminal Code (KUHP), Law No. 51 of 1960 concerning the basis of Agrarian Principles. While secondary data is like the writings of scientists in the form of journals, theses, other scientific works related to the research title. The results of the study show that the control of land over other people's property is generally regulated in the Criminal Code Law Article 385 Land grabbing over land rights in a broad sense is also regulated in Law No. 51 of 1960 (Perpu) concerning the prohibition of using land without a permit Those who are entitled to the land are contained in Articles 2 and 6. So, in this case the act of controlling land over other people's property rights can be punished as regulated in the laws and regulations. Thus it is hoped that law enforcers will make decisions against the perpetrators of crimes in accordance with existing regulations.